ANALISIS SELISIH SUHU KOMPONEN PANEL LVMDP MENGGUNAKAN ALAT INFRARED THERMOGRAPHY DI PT. DONGJIN INDONESIA - Rovino Alghafari; Desmira Desmira (Pusat Penelitian dan Pengabdian Masyarakat, 2026)
Low Voltage Main Distribution Panel (LVMDP) is a vital component in industrial electrical distribution systems. Its main function is to regulate the central power line for all equipment in an industrial production facility. Because of its very important role, every component inside the LVMDP needs to be monitored intensively. This panel operates under a heavy load, causing its temperature to rise. One method to maintain the condition of the LVMDP is by using infrared thermography equipment. PT. Dongjin Indonesia utilizes this tool to monitor the temperature of each component in the panel. The temperature of these components can be monitored directly. The measurement results show a temperature difference of 26.5 °C, with the lowest temperature reaching 4 °C. This temperature is still well below the minimum operating temperature limit of 50 °C. This indicates that the components of the LVMDP panel at PT. Dongjin Indonesia is in optimal condition and ready to continue operating. By regularly monitoring the temperature, the company can prevent damage that could disrupt productivity and the safety of the production process. Thus, the use of infrared thermography provides significant advantages in maintaining the performance of LVMDP and ensuring the smooth operation of the industry.